Levodopa induced hyponatremia in an elderly patient - Magri, Chantelle; Cordina, John (International Journal of Research in Medical Sciences, 2024)
Hyponatremia is one of the most common electrolyte abnormalities encountered in clinical practice. Older persons have an increased risk of developing hyponatremia due to multimorbidity and frequent polypharmacy. We present a case of hyponatremia induced by levodopa in an 87-year-old lady not suffering from Parkinson’s disease. This case highlights an important iatrogenic cause of hyponatremia and its sequelae.